IoT-based Smart Agriculture Field Monitoring using Arduino Nano - T., Devika; N., Santhiyakumari; J., Nagaraj; K., Arun S; T., Sam Sundhar; K., Siva Sakthi (IRO Journal on Sustainable Wireless Systems, 2024)
The rapid developments in the Internet of Things (IoT) have enabled even individuals with limited technical knowledge to access real-time reception of information conveniently at their doorstep. Agriculture, one of the necessities for human livelihood, has been significantly enhanced with technological advancements. The study proposes an IoT-based smart agriculture field monitoring system using Arduino Nano. The device provides real-time data on temperature and soil moisture content for cultivating crops like paddy, tapioca, turmeric, etc. The system also allows farmers to get remote access to the irrigation systems, hence improving the management of the fields along with their resources.
Keywords: IoT; Sensors; ThingSpeak App; Agriculture